Prevalence of visual art education in medical school curricula: a national survey of US medical schools - Sally Nijim; Isra Hamdi; Stephanie Cohen; Joel T. Katz; Ingrid M. Ganske (Medical Education Online, 2023)
ABSTRACTBackground: The Association of American Medical Colleges (AAMC) has recommended integrating medically-relevant arts and humanities curricula into medical student education in order promote physician skills development. An analysis of the state of existing visual arts-based medical school pedagogies was conducted to inform future implementation strategies.Methodology: An electronic survey was distributed to representatives of US medical schools to describe the prevalence and characteristics of visual arts-based medical school curricula. Official courses, informal events, cross-registration opportunities, and established art museum partnerships were assessed.Results: Survey response rates were 65% for US allopathic medical schools and 56% for osteopathic medical schools. A majority (79%) of responding institutions incorporate or support medical student art experiences in some format. Thirty-one percent (n = 36) of schools offer stand-alone humanities courses using visual arts. These were primarily allopathic programs (n = 35; 37% of allopathic programs) and only one responding osteopathic program (n = 1; 5% of osteopathic programs). Schools without dedicated courses are less likely to report other curricular and extracurricular visual arts engagement. Most visual art medical courses are offered at medical schools located in the Northeastern United States.Conclusions: Many but not all medical schools are incorporating the visual arts into their medical education curriculum. Opportunities to promote increased uptake, more effective implementation, and collaboration strategies for the AAMC recommendations are proposed.